Analisis Kesulitan Siswa Dalam Pemecahan Masalah Soal Cerita Matematika Pada Siswa Smp Kelas VII Di SMP N 2 Gatak Sukoharjo - Sulistiyorini, Sulistiyorini; , Dra. N. Setyaningsih, M.Si (2016)
The aim of this research is describing the students difficulties in solving mathematic story questions in junior high school students viewed from the aspect of understanding the problem, planning, implementing, and correcting. The type of this research is qualitative research. The time in conducting this research is at the second semester, academic year 2015/2016. The subject research is the students of VII A SMP N 2 Gatak, Sukoharjo. The techriques of collecting data are written test, interview, and documentation. The validity data uses triangulation of source and method. The result of this research are: (1) difficulties in problem understanding aspect that students are not accustomed to do story questions with problem solving steps of Polya, students have mistakes in writing symbol, they do not understanding about the concept yet, and students cannot manage the prosess well. (2) planning aspect difficulty that students cannot make mathematic model yet and the students ability is low in understanding problem, and also lack of excercises. (3) implementing aspect difficulty that students are innaccurate in counting the steps are too long, and having mistake in mathematic model making. (4) correcting aspect difficulty, that students do not know how to corret it, students unable to manage the time well, and the attitude of students double check the answer that do not.